Crystal structure of bis[μ-bis(diphenylphosphanyl)methane-κ2P:P′]digold(I) dichloride acetone monosolvate monohydrate - Yeo, C.I.; Tan, Y.S.; Tiekink, E.R.T. (International Union of Crystallography, 2015)
In the title complex salt, [Au2{(C6H5)2PCH2P(C6H5)2}]Cl2·(CH3)2C=O·H2O, the dication forms an eight-membered {-PCPAu}2ring with a transannular aurophilic interaction [Au···Au = 2.9743 (2) Å]. The ring approximates a flattened boat conformation, with the two methylene C atoms lying ca 0.58-0.59 Å above the least-squares plane defined by the Au2P4atoms (r.m.s. deviation = 0.0849 Å). One Cl-anion functions as a weak bridge between the AuIatoms [Au···Cl = 2.9492 (13) and 2.9776 (12) Å]. The second Cl-anion forms two (water)O-H···Cl hydrogen bonds about a centre of inversion, forming a centrosymmetric eight-membered {···HOH···Cl}2supramolecular square. Globally, the dications and loosely associated Cl-anions assemble into layers lying parallel to the ac plane, being connected by C-H···Cl,π(phenyl) interactions. The supramolecular squares and solvent acetone molecules are sandwiched in the inter-layer region, being connected to the layers on either side by C-H···Cl,O(acetone) interactions.